El tamp en valencià - Calvo Pérez, Julio (Caplletra. Revista Internacional de Filologia, 1995)
This essay intends to apply to the Valencian verb the linguistic method of TAMP (tense-aspect-mood-person) within which different pragmatic parameters are organized in such a way never before seen to better understand this phenomena. The basic theory that this application shows is the Topological-Natural Pragmatics (T-NP, Calvo 1989) in which the tense-aspect relationship is dominated by the super-structural mood-person relationship. In this way, a new verbal paradigm is offered to explain the necessity of the past periphrastic or of the marked first person of the present indictive. The explanation of TAMP in Valencian is based in morphology, since there exists morphems which characterize it: stress (—'(—), —(—')), aspect (-av-I-i-), mood (- Vr-) and supermood (-Vs-). When the morphems do not appear, the result is a general background that permits different verbal uses and their neutralizations.